The cost of helping: An exploration of compassionate responding in children. (10th June 2018) - Green, Mitchell; Kirby, James N.; Nielsen, Mark
Abstract : Children engage in prosocial behaviour from an early age. Whether children will reliably provide compassionate help to a suffering individual is unclear. To investigate this, 73 4‐years‐olds were presented with three novel tasks in which they and a puppet had opportunity to win stickers by completing respective versions of the same tasks. In all cases, the puppets were unable to complete their tasks. The puppets 'reacted' by being either upset or not upset. While children provided help when it did not cost them, their inclination to do so was significantly diminished when it incurred a personal cost. Statement of contribution What is already known on this subject? Children are generally prosocial and altruistic. Personal cost can inhibit prosocial helping in children. What does this study add? We created two conditions (distress vs. no distress) and (cost vs. no cost) to examine the difference between prosocial and compassionate helping. We obtained first evidence that children will not respond compassionately when incurring a personal cost.